PRESENTATION OF A PHYSICAL EXAMINATION PROTOCOL (BIOMAGNETIC OR BIOENERGETIC SCREENING) AND SEMIOLOGY FOR THE APPLICATION OF THE MEDICINAL BIOMAGNETISM TECHNIQUE: NARRATIVE REVIEW - Maria Rambo Corrêa, Letícia; Rambo, Rui; Chudek Rambo, Marilene; Mara Rambo Martini, Angela; Maria Oliveira Lima, Márcia; Viapiana Bossa, Adriane (Health and Society, 2023)
Medicinal Biomagnetism (BM) has os its founder Dr. Isaac Goiz Durán, and as a proposal, to be an integrative and complementary therapeutic measure in health, in a comprehensive and universal way. However, as it is generally disseminated through free courses, it is subject to interpretation and application bias in the identification of tracking points and Biomagnetic Pairs (PBMs). Clinical Protocols and Therapeutic Guidelines establish criteria for health management in any clinical specialty. The objective of this study is to present a proposal for the standardization of a physical examination (screening) and semiology protocol for BM, in a structured and systematized way, aiming to provide a standard language for Biomagnetists and an adequate guideline for investigations and scientific evidence. A narrative review was used to support this proposal. The protocol proposed in this study originates from the works developed by its founder, and is presented in a segmented way, in four columns, for better visualization. The columns show the divisions with the classification of PBMs, the tracking points and their anatomical location, the impaction or resonance points and their anatomical location, and finally, a column with the symptomatology and symptomatological specification of the PBMs. What is observed in this review is the organized arrangement of the screening points and other important information for an adequate application and investigation of the technique. Thus, the present study is relevant in presenting a proposal for a structured and systematized protocol, for a better understanding of professionals who work in the application of the technique, patients and the scientific community. This opens up perspectives that this protocol can serve as a research base and the BM reaches the desired robust scientific evidence, and that it is recognized and included as an integrative and complementary practice in structured public and private health services.